PENERAPAN SYARI’AT ISLAM PADA SISTEM MULTI LEVEL MARKETING SYARI’AH HERBA PENAWAR AL WAHIDA (HPA) STUDI KASUS DI PEKANBARU - Nur Intan (Sekolah Tinggi Pariwisata Mataram, 2020)
Herba's firm Al Wahida's Bidder (HPA) are corporate one move at doctor sell areas an herbs by uses Multi's sell system Marketing Syariah's Levels . There is aim even of research to know how Multi's system Marketing Syariah Herba's level Al Wahida's Bidder (HPA), any kind resistor factor in Multi's performing Marketing Syariah Herba's Level Al Wahida's Bidder (HPA), and how economic analysis Islamicing to Multi's system Marketing Syariah Herba's Level Al Wahida's Bidder (HPA). This observational location gets address at Jl. Jend. Sudirman No. 168 Pekanbaru Pekanbaru Telp (0761) 24108. There is method even data collecting that is utilized in this research is interview, observation, bibliographical research, documentation. Technics data analysis utilizes kualitatif's descriptive analytic-method, meanwhile technics inscriptive data which is deductively, inductive, descriptive analytic. Population in observational it is branch member HPA Pekanbaru that total 100 person. Of that amount researcher takes sample as big as 30 %. Methodics sample take which is Random is sampling. Observational finding at the site declares for that Multi's system Marketing Syariah Herba's Level Al Wahida's Bidder (HPA) are may, since doesn't contain element ghoror or fraud, according to syari’at islam, and kosher warrantee product. But upon currently so a lot of MLM'S system amends and one takes after MLM as system of PYRAMID, MONEY IS GAME, so society is hard to differentiate it. On eventually member HPA there are many that passive deep going that MLM'S network. Corporate party also still reducing in give good grasp to member about MLM Syari ’ ah, and its reducing HPA'S product socialization to society is added again at the price it what do come under precious at product appeal a sort another makes consumers tend to choose cheaper product despite of kehalalan and its quality is still at hesitates.